Trends and outcomes of mechanically ventilated cirrhotic patients in the United States from 2005–2014. (May 2022) - Cheung, Kyle; Mailman, Jonathan F; Crawford, Jennifer J; Karvellas, Constantine J; Sy, Eric
Purpose: Cirrhotic patients in organ failure are frequently admitted to intensive care units (ICUs) to receive invasive mechanical ventilation (IMV). We evaluated the trends of hospitalizations, in-hospital mortality, hospital costs, and hospital length of stay (LOS) of IMV patients with cirrhosis. Methods: We analyzed the United States National Inpatient Sample from 2005–2014. We selected discharges of IMV adult (≥18 years) patients with cirrhosis using the International Classification of Diseases, 9th Edition, Clinical Modification codes . Trends were assessed using linear regression and joinpoint regression. Results: Between 2005 and 2014, there were approximately 9, 441, 605 hospitalizations of IMV adult patients, of which 4.7% had cirrhosis. There was an increasing trend in the total number of IMV cirrhotic patient hospitalizations (annual percent change [APC] 7.0%, 95% confidence interval [CI] 6.4%; 7.6%, Ptrend  < 0.001). The in-hospital case-fatality ratio declined between 2005–2011 (APC –2.9%, 95% CI, –3.4%; –2.4%, Ptrend  < 0.001); however, it remained similar between 2011–2014 ( Ptrend  = 0.58). The total annual hospital costs of all IMV cirrhotic patients increased from approximately $1.2 billion USD in 2005 to $2.7 billion USD in 2014 ( Ptrend  < 0.001). The mean hospital costs per patient and mean LOS declined between 2005 and 2014 ( Ptrend  < 0.001 and Ptrend  = 0.01 respectively). Conclusions: The total number of hospitalizations and total annual costs of IMV patients with cirrhosis have been increasing over time. However, past hesitancy around admitting cirrhotic patients to the ICU may need to be tempered by the improving mortality trends in this patient population.